THE EFFECTS OF TWO COMPUTERIZED PROGRAMS IN REDUCING JORDANIAN TERTIARY STUDENTS SPELLING ERRORS - Al-zuoud, Khalid (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
This study investigated the effects of using two computerized programs on reducing the spelling errors Jordanian tertiary students. Ginger and Microsoft Word 2007 were used as two modes of presentation. These programs represented the textaudio and text modes, respectively, according to the modality principle. The spelling error levels (i.e., high, medium, and low) of the students were compared. This study was conducted based on Mayers cognitive theory of multimedia learning, dual route theory of efficient spelling, and spelling in the context approach. The modality principle was similarly used as an effective tool for improving the spelling performance and reducing the spelling errors of students. The study sample comprised 80 male and female second-year students who were purposefully selected from Hashemite University in Jordan. Both study groups took pre- and post-tests as well as participated in structured interviews to answer the main questions of the study. The spelling errors of these Jordanian students were classified into four types according to Cooks classification. the interference between the Arabic and English languages was clarified. The phonological differences between these languages may cause many spelling mistakes that may also affect how students pronounce words. The modality principle must be integrated into the instructional, curriculum, computer-based, and web-based designs to help students develop their spelling performance. EFL professors are encouraged to use programs with contextual spelling features for teaching their students how to spell. Future studies must investigate the effects of these contextual features on other language skills, such as pronunciation, grammar, and vocabulary. These studies must also measure the effects of using computerized programs on how students pronounce words.